ACT-5 Prognosis of IDH-mut lower-grade gliomas in Hokkaido University Hospital. (6th December 2021) - Yamaguchi, Shigeru; Ishi, Yukitomo; Okamoto, Michinari; Sawaya, Ryousuke; Motegi, Hiroaki; Kobayashi, Hiroyuki; Terasaka, Shunsuke; Fujimura, Miki
Abstract: Background: WHO grade 2 and 3 adult gliomas are nowadays getting together as lower-grade gliomas (LrGGs), but we had been recognized grade 3 (G3) tumors as high-grade and grade 2 (G2) tumors as low-grade. In this report, we investigate the treatment and prognosis of the patients with LrGG harboring IDH mutations in our institutions. Methods:We retrospectively review primary treatments and their prognosis for LrGG patients with IDH mutation since 2003. They categorized as astrocytomas and oligodendrogliomas according to 1p/19q loss-of-heterozygosity status. Prognosis were evaluated by overall survival. Postoperative primary treatments applied chemo-radiotherapy (CRT), radiotherapy only (RT), chemotherapy only (CT), and observation (Ob). Results: 36 astrocytomas and 60 oligodendrogliomas were identified. In astrocytomas, the patients with G3 (N=16) were treated by CRT (N=14) or CT (N=2), and the patients with G2 (N=20) were treated by CRT (N=2), RT (N=3), CT (N=3), or Ob (N=12). In oligodendrogliomas, the patients with G3 (N=34) were treated by CRT (N=32) or CT (N=2), and the patients with G2 (N=26) were treated by CRT (N=3), RT (N=1), CT (N=5), or Ob (N=17). 10-year survival rate (10yOS) of astrocytomas and oligodendrogliomas are 54% and 90%, respectively (p=0.002). According to histological malignancy, 10yOS of G3 and G2 astrocytomas were 54% and 54%, respectively (p=0.97) and that of G3 and G2 oligodendrogliomas were 86% and 100%, respectively (p=0.64). In both group, there are no different of prognosis according to histological malignancy. Discussion: There was no prognostic different between G2 and G3 astrocytomas in our institution. Since the treatment intensity for G2 and G3 astrocytomas were clearly different, the primary treatment for G2 astrocytomas might be insufficient. On the other hand, there were no prognostic different between G2 and G3 oligodendrogliomas in our institution, as with recent reports, so the primary treatment intensity for oligodendrogliomas should be appropriate.